Analysis of the Effect of Age on the Absorption Dose of X-ray Radiation in Thorax Examination - Mukholiq Fathunnisa; Pratiwi Sri Wardani; Devina Rayzy Perwitasari (Jurnal Inotera, 2023)
This research aimed at finding out the effect of the patient's age on the absorbed dose obtained during the thorax examination. The observation data used is the exposure factor in the form of the tube voltage (kV), tube current (mA), irradiation time (s), and focus film distance (cm). The age range used is grouped based on the elderly age category established by the Ministry of Health of the Republic of Indonesia which ranges from 46 years until 85 years of age. From the data on the exposure factor and age of elderly patients, the oneway ANOVA statistical test was conducted. From the results of these statistical tests, the results obtained FCalculate value is 0,201 and sig 0,821 for Thorax AP examination and the results obtained FCalculate value is 0,790 and sig 0,476 for Thorax PA examination with the FTable value is 3,81 and the sig is 0,05. Therefore, based on the testing criteria in statistics of the initial hypothesis (H0) is accepted or it can be concluded that age does not affect the amount of X-ray radiation absorbed dose received by elderly patients in thorax examinations from the age range of 46 years until 85 years.